1999
DOI: 10.1016/s0009-9236(99)70037-8
|View full text |Cite
|
Sign up to set email alerts
|

Population distribution and effects on drug metabolism of a genetic variant in the 5′ promotor region of CYP3A4

Abstract: This promotor region polymorphism does not appear to play a major role in determining constitutive CYP3A4 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
116
3
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(131 citation statements)
references
References 28 publications
11
116
3
1
Order By: Relevance
“…Comparing the frequency of the G allele (0.15) with those reported by other studies, we see a similarity with Brazilian population (0.13) (Cavalli et al), Asian (0.16) (Thompson et al) and Hispanic (0.09) (Ball et al, 1999), and the frequency of the mutant variant CYP3A4*1B was significantly higher than that observed in Europeans (0.05) (Sata et al, 2000) and American population, both white (0.04) and Black (0.54) (Ball et al) and lower in Africans (0.82) (Zanger et al, 2008) and Afro-American (0.67) (Sata et al). Gao et al (2008) demonstrated an association between the presence of G allele in hypercholesterolemic individuals who had a greater reduction of total cholesterol levels, when treated with atorvastatin 20 mg/day for 4 weeks in Asiatic population.…”
Section: Discussionsupporting
confidence: 82%
“…Comparing the frequency of the G allele (0.15) with those reported by other studies, we see a similarity with Brazilian population (0.13) (Cavalli et al), Asian (0.16) (Thompson et al) and Hispanic (0.09) (Ball et al, 1999), and the frequency of the mutant variant CYP3A4*1B was significantly higher than that observed in Europeans (0.05) (Sata et al, 2000) and American population, both white (0.04) and Black (0.54) (Ball et al) and lower in Africans (0.82) (Zanger et al, 2008) and Afro-American (0.67) (Sata et al). Gao et al (2008) demonstrated an association between the presence of G allele in hypercholesterolemic individuals who had a greater reduction of total cholesterol levels, when treated with atorvastatin 20 mg/day for 4 weeks in Asiatic population.…”
Section: Discussionsupporting
confidence: 82%
“…The rs2740574 SNP is in the promoter region of the gene, but efforts to show a functional effect of this variant have proved difficult. Spurdle et al (2002) evaluated multiple reporter gene constructs, but found no differences in the transcription between the putative disease and wild-type allele; the results of other functional studies have been equivocal (Ball et al, 1999;Westlind et al, 1999;Amirimani et al, 2003;Rodriguez-Antona et al, 2005). Alternatively, it may be that rs2740574 is simply in linkage disequilibrium with the causal variant, which remains to be identified.…”
Section: Discussionmentioning
confidence: 97%
“…However, a polymorphism, which plays a significant role in the activity of CYP3A4, has not yet been identified in the 5 0 -regulatory region of the CYP3A4 gene. 24 Therefore, we have focused on human PXR (hPXR) as a factor effecting CYP3A expression and identified splicing variants of hPXR as a possible factor in interindividual variation caused in CYP3A activity. 25 Interestingly, we have found that mRNA expression of wild-type hPXR is well correlated with mRNA expression of CYP3A4 in liver sample (unpublished data), which is consistent with the recent report.…”
Section: Discussionmentioning
confidence: 99%